Sustainable flood risk and stormwater management in blue‐green cities; an interdisciplinary case study in Portland, Oregon - O’Donnell, Emily C.; Thorne, Colin R.; Yeakley, J. Alan; Chan, Faith Ka Shun (2020)
Blue-Green Infrastructure (BGI) is recognized as a viable strategy to manage stormwater and flood risk, and its multifunctionality may further enrich society through the provision of multiple cobenefits that extend far beyond the hydrosphere. Portland, Oregon, is an internationally renowned leader in the implementation of BGI and showcases many best practice examples. Nonetheless, a range of interdisciplinary barriers and uncertainties continue to cloud decision making and impede wider implementation of BGI. In this paper, we synthesize research conducted by the “Clean Water for All” (CWfA) research project and demonstrate that interdisciplinary evaluation of the benefits of Portland’s BGI, focusing on green street bioswales and the East Lents Floodplain Restoration Project, is essential to address biophysical and sociopolitical barriers. Effective interdisciplinary approaches require sustained interaction and collaboration to integrate disciplinary expertise toward a common problem-solving purpose, and strong leadership from researchers adapt at spanning disciplinary boundaries. While the disciplinary differences in methodologies were embraced in the CWfA project, and pivotal to providing evidence of the disparate benefits of multifunctional BGI, cross-disciplinary engagement, knowledge coproduction, and data exchanges during the research process were of paramount importance to reduce the potential for fragmentation and ensure research remained integrated. © 2020 The Authors. Journal of the American Water Resources Association published by Wiley Periodicals LLC on behalf of American Water Resources Association